The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1101/608703
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Amygdala controls saccade and gaze physically, motivationally, and socially

Abstract: Highlights-Central amygdala facilitates contralateral saccades selectively. -Saccade facilitation is related to motivational goals and social interaction. -The amygdala thus controls goal-directed behavior based on emotional contexts. AbstractThe amygdala is uniquely sensitive to emotional events. However, it is not understood whether and how the amygdala uses such emotional signals to control behavior, especially eye movements. We therefore injected muscimol (GABA A agonist) into the central nucleus of amygda… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…Together with our previous findings (Maeda et al, 2018(Maeda et al, , 2019, these results suggest that the amygdala governs social and emotional behaviors at multiple levels. At the most general level, the amygdala mediates contextappropriate social orienting, as evidenced by the effect of amygdala inactivation during movie free viewing (Maeda et al, 2019). At a more fine-grained level, the amygdala selectively mediates the spatially oriented action required for finding objects of interest quickly and accurately.…”
Section: Ll Open Access Isciencesupporting
confidence: 86%
See 3 more Smart Citations
“…Together with our previous findings (Maeda et al, 2018(Maeda et al, , 2019, these results suggest that the amygdala governs social and emotional behaviors at multiple levels. At the most general level, the amygdala mediates contextappropriate social orienting, as evidenced by the effect of amygdala inactivation during movie free viewing (Maeda et al, 2019). At a more fine-grained level, the amygdala selectively mediates the spatially oriented action required for finding objects of interest quickly and accurately.…”
Section: Ll Open Access Isciencesupporting
confidence: 86%
“…Our data showed that inactivation of the amygdala suppressed oculomotor behaviors. However, this effect might be caused by the inactivation of surrounding areas, especially the caudal-ventral part of the putamen, which we call ''putamen tail (PUTt)'' where neurons encode stable object values (Kunimatsu et al, 2019). We thus injected muscimol in PUTt unilaterally (monkey S: n = 3, monkey D: n = 4) (Figure S2A).…”
Section: Suppression Of Saccades By Amygdala Inactivationmentioning
confidence: 99%
See 2 more Smart Citations